Influences of Korean Wave on the Intention of Visiting Korea in Generation Y Malaysia - Mah, Han Poh (2016)
Recently, Korean Wave had become one of the popular cultures through globalization. The purpose of the study is investigating the relationship between the influences of Korean Wave on the intention of visiting Korea in Generation Y Malaysia. There is a limited literature review which is regarding the consumer behaviour of Generation Y based on the influence of Korean Wave especially in Malaysia. According to Lee-Yook et al. (2014) that Korean Wave mainly refers to few predominant types to reflect the Korean popular culture which are television drama series (K-drama), Korean popular music (K-pop), Korean idol group, actor and singer (K-artist) and Korean food (k-food). Korean wave had been figured as West-centred globalization and proved that the globalisation is a two-way flow but not just only a one-way traffic (Yoon, 2016). The research methodology is used correlation which is a quantitative survey to study the relationship between the independent and dependent variables in order to get the extent of the relationship whether the relationship exist. The data collection had been conducted through online questionnaire and 250 respondents had been acquired with the snowball sampling method. From the research findings, K-pop is the only factor that unable to create the intention for the Gen Y Malaysia for visiting Korea. The K-drama has the highest influence as a factor for attracting Gen Y for visiting Korea. Therefore, the hypothesis that regarding the K-pop will create the intention for Gen Y Malaysia for visiting Korea had been rejected. The rest of the factors will have a significant relationship towards the intention for visiting Korea.